مبادئ الجنائيات الإسلامية وتطبيقها فى السياق الإندونيسي (JOURNAL OF INDONESIAN ISLAM, 2013)
The issue of Islamic criminal law and its application has become a somewhat heated issue in Indonesia since the very advent of this nation. The political and academic circles are among those who have intensively been involved in debating this problem. The intensity of the debate is due to the fact that the issue is closely related not only to the social construct of the society but also with the very nature of the national law. Speaking of Islamic law in other words, would put a lot of question on how it fits into the national law. This paper deals with this complexity by looking at the Islamic law both as a pure theory and as a formal law that may be applied in certain context. As a pure theory, the Islamic law is dealt with here as vision and idea concerning the attitude of human being in a given society, while as an applied cannon the Islamic law is believed to have the practical dimension that may be applied in a particular situation. The fact that Islamic law has a practical dimension -this paper argues- implies that Shari‘ah is none other than the product of social dynamics. And this would further mean that the the intellectual exercise to draw legal dictum must take into account the human interest (maslahah) on the one hand, and the dialectic between text and context on the other.